Optimal routes of administration, vehicles and timing of progesterone treatment for inhibition of delivery during pregnancy - Fang, Dajun; Kuon, Ruben-Jeremias (European journal of obstetrics & gynecology and reproductive biology, 2017)
Progestins, notably progesterone (P4) and 17 alpha hydroxyprogesterone caproate, are presently used to treat pregnant women at risk of preterm birth. The aim of this study was to assess the optimal treatment options for progesterone (P4) to delay delivery using a sensitive bioassay for progesterone.
Gesehen am 20.11.2018